Computational Strategies for Protein-Surface and Protein-Nanoparticle Interactions - Brancolini, Giorgia; Polzi, Laura Zanetti; Corni, Stefano (Journal of Self Assembly and Molecular Electronics, 2023)
Protein-nanoparticle associations have important applications in nanoscience and nanotechnology but the recognition mechanisms and the determinants of specificity are still poorly understood at the microscopic level. Crucial questions remain open, related to the association mechanisms, control of binding events, and preservation of functionality. Gold is a promising material in nanoparticles for nanobiotechnology applications because of the ease of its functionalization and its tunable optical properties. We present a concise overview of recent computational modeling advances which were pursued in the quest for a theoretical framework elucidating the association mechanisms and the ability to design and control the recognition events of a specific class of systems, namely, interfaces between polypeptides/proteins and a gold surface in the presence of water. We select two different methodological advances, the first related to the effect of surfactants covering the surface of nanoparticles and altering their interactions with proteins and the second related to the immobilization of proteins on inorganic surfaces and conserving their functionality. Both cases, demonstrate how the understanding of the polypeptide-surface coupling mechanisms is essential to the control of the process and exploitation for biotechnological and nanotechnological purposes.